2015
DOI: 10.1016/j.applthermaleng.2015.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of a solar-assisted OTEC cycle for power generation and fishery cold storage refrigeration

Abstract: 15The cold storage in fishery industry is in great demand in tropical coastal regions. This research 16 proposes an ocean thermal energy conversion (OTEC) based solar-assisted combined power and 17 refrigeration cycle, which can be used for both electricity generation and fishery cold storage 18 application. In this proposed combined cycle, the ammonia/water is selected as the working fluid and 19 the warm/cold seawater is utilized as the heating/cooling source. A two-stage ejector system is 20 2 introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In the present work, the selections of boundary conditions are based on the operating conditions of OTEC systems. As shown in Yuan et al, [9,10] the evaporation temperature for ammonia vapour is lower than 60 C for the OTEC system coupled with solar energy. Considering pressure losses, we adopted As the secondary inlet of the ejector is connected to the turbine, a 1 MPa pressure drop was assumed for all cases in this work.…”
Section: Fluid Properties and Boundary Conditionsmentioning
confidence: 85%
See 1 more Smart Citation
“…In the present work, the selections of boundary conditions are based on the operating conditions of OTEC systems. As shown in Yuan et al, [9,10] the evaporation temperature for ammonia vapour is lower than 60 C for the OTEC system coupled with solar energy. Considering pressure losses, we adopted As the secondary inlet of the ejector is connected to the turbine, a 1 MPa pressure drop was assumed for all cases in this work.…”
Section: Fluid Properties and Boundary Conditionsmentioning
confidence: 85%
“…The authors also used a flat-plate solar collector to increase the heating source temperature, which improved the efficiency of the OTEC. [10] The numerical results indicated that the comprehensiveproduction efficiency was 7.89% for the new system.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, a new type of microalgae-bacterial biological fuel cell (MBBFC) was designed for aquaculture wastewater treatment and energy recovery [ 121 ]. Since fishery refrigeration consumes more energy in fishery activities, Yuan et al [ 122 ] proposed the use of a solar-assisted hybrid power generation and refrigeration cycle system based on ocean thermal energy conversion (OTEC) to provide power for fishery refrigeration and reduce the power pressure related to refrigeration. Using a self-powered electrochemical water treatment system with a triboelectric nanogenerator (TENG) combined with seawater electrolysis technology, the energy consumption and costs of algae removal and sterilization in fishery were effectively reduced [ 123 ].…”
Section: Research Status At Home and Abroadmentioning
confidence: 99%
“…9 Water-ammonia mixture is one of the most efficient known zeotropic mixtures that is applied frequently as the working fluid of combined plants. 10,11 Yuan et al 12 proposed a combined ammonia-water power cycle and a refrigeration cycle integrated with a solar system. They demonstrated that ammonia-water with higher concentrations improved the performance of the proposed system.…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al 12 proposed a combined ammonia‐water power cycle and a refrigeration cycle integrated with a solar system. They demonstrated that ammonia‐water with higher concentrations improved the performance of the proposed system.…”
Section: Introductionmentioning
confidence: 99%